First record of Brachymeria pandora (Crawford, 1914) and Conura aff. flavicans Spinola, 1837 (Hymenoptera, Chalcididae) in cocoon of Rothschildia erycina (Shaw, 1796) (Lepidoptera, Saturniidae): multiparasitoidism or hyperparasitoidism? - Lourido, Gilcélia M.; Tavares, Marcelo T.; Galvão, Amanda; Oliveira, Marcio L. de (Entomological Communications, 2025)
We report the first record of the parasitoid Brachymeria pandora (Crawford, 1914) (Hymenoptera, Chalcididae) emerging from a cocoon of Rothschildia erycina (Shaw, 1796) (Lepidoptera, Saturniidae). This interaction was observed on Eriotheca candolleana (K. Schum.) A. Robyns (Malvaceae), which also constitutes the first record of this plant as a host for R. erycina. These findings are from Alter do Chão, Santarém, state of Pará, Brazil. Additionally, a female of Conura aff. flavicans Spinola, 1837 (Hymenoptera: Chalcididae) was observed exhibiting oviposition behavior on the same cocoon, from which the pupa responded with a trembling defensive reaction, but no individuals of this species were obtained. However, no individuals of C. aff. flavicans emerged, and its role as a primary parasitoid of the moth or a hyperparasitoid of B. pandora is discussed.